Genome-wide analysis for the melatonin trait associated genes and SNPs in dairy goat (Capra hircus) as the molecular breeding markers - Wu, Hao; Yi, Qi; Ma, Wenkui; Yan, Laiqing; Guan, Shengyu; Wang, Likai; Yang, Guang; Tan, Xinxing; Ji, Pengyun; Liu, Guoshi (Frontiers in Genetics, 2023)
Previous studies have reported that the endogenous melatonin level is positively associated with the quality and yield of milk of cows. In the current study, a total of 34921 SNPs involving 1177 genes were identified in dairy goats by using the whole genome resequencing BSA analysis to match the melatonin levels of the dairy goats to the SNPs, we have ident 3 SNPs which significantly correlate with melatonin levels. These 3 SNPs include CC genotype 147316, GG genotype 147379 and CC genotype 1389193. These SNPs locate in the exon regions of ASMT and MT2 genes. Dairy goats with these SNPs have approximately 5 fold-higher melatonin levels in milk and serum than the average melatonin level detected in the current goat population. If the melatonin level impacts the milk production in goats as in cows, the results strongly suggest that these 3 SNPs can serve as the molecular marker to select the goat breading that has the improved milk quality and yield. This is a goal of our future study.